Association study of polymorphisms rs4552569 and rs17095830 and the risk of ankylosing spondylitis in a Taiwanese population. - James Cheng-Chung Wei (Public Library of Science (PLoS), 2013)
Ankylosing spondylitis (AS) is a chronic inflammation of the sacroiliac joints, spine and peripheral joints. However, the development of anklosing spondylitis is unclear. Human leukocyte antigens HLA-B27 and ERAP1 have been widely reported to be associated with AS susceptibility. A recent genome-wide association study (GWAS) showed that two new susceptibility loci between EDIL3 and HAPLN1 at 5q14.3 (rs4552569) and within ANO6 at 12q12 (rs17095830) contribute to the risk of AS in Han Chinese. In this study, we enrolled 475 AS patients and 475 healthy subjects to assess whether these genetic variations contribute to the susceptibility and the severity of AS in the Taiwanese population. The correlation between genetic polymorphisms, AS activity indexes, (namely, BASDAI, BASFI and BAS-G) and AS complications (uveitis and inflammatory bowel disease) were tested using the markers, rs4552569 and rs17095830. Although no association between rs4552569/rs17095830 genetic polymorphisms and AS susceptibility/severity was found, a significant association between rs17095830 and inflammatory bowel disease was observed in a Taiwanese population.